TYPES AND INTERPRETATION OF THE UZBEK NATIONAL PUN (Scientific journal of the Fergana State University, 2023)
This article focuses on the Uzbek national word clench as pun, its types and specific features. In particular, such types as “phonostilistic pun”, “phonographic pun”, “lexical-semantic pun”, “morphological pun”, “syntactic pun”, manifested in the language levels are subject of analysis from a linguistic point of view.